The Consequences of Overqualification on Job Outcomes: Challenges, Recommendations, and Future Directions for Mitigation - Dr. Junaid Athar Khan,; Dr. Syed Noman Mustafa,; Dr. Sonia Sethi,; Dr. Azhar Khan, (Dialogue Social Science Review (DSSR), 2025)
This study discusses the subject of over qualification and job outcomes, the subsequent challenges it presents, and possible recommendations and future directions towards remediation. By definition, over qualification exists when an employee's skills, education, or experience are much more advanced than what is needed for a job. Job misalignment produces various adverse effects on job satisfaction, employee motivation, performance, and retention rates. This paper identifies several challenges facing overqualified employees: a sense of frustration, falling levels of engagement at work, and a sense of underutilization. Such challenges affect both individual wellness and the larger organizational culture and productivity. Employees who are overqualified report a low number of job satisfaction figures and high turnover intentions to face higher recruitment and training costs by organizations. Several recommendations for tackling those challenges comprise the study. Organization-wide employee support programs should endorse free discussion with the creation of possible projections involving employees for their future career aspirations and possibilities for utilizing their skills best. Effective job designs will also permit increased role flexibility and access to challenging opportunities for carrying out employees' skills. Organizations may also create an organizational culture of continuous learning and development through which employees qualify for career advancements using skills that match their learning qualifications. It is highly recommended for regular evaluations of the job roles and expectations to ensure their alignment with the capabilities of employees. Directions for future research may take the shape of longitudinal studies assessing how over qualification impacts job outcomes in the short term and the success of strategies employed. Cross-industry comparisons might reveal how different sectors manage over qualification.